Micro and Smart Devices and Systems - Vinoy, K. J.; Ananthasuresh, G. K.; Pratap, Rudra; Krupanidhi, S. B.; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2014)
The book presents cutting-edge research in the emerging fields of micro, nano, and smart devices and systems from experts working in these fields over the last decade. Most of the contributors have built devices or systems or developed processes or algorithms in these areas. The book is a unique collection of chapters from different areas with a common theme and is immensely useful to academic researchers and practitioners in the industry who work in this field.
Microsensors: Design, Development, Fabrication, Packaging, and Testing of MEMS Pressure Sensors for Aerospace applications -- MEMS Piezoresistive Accelerometers -- A Handheld Explosives Detector Based on Amplifying Fluorescent Polymer -- Development of a Surface Plasmon Resonance (SPR) Based Bio sensing System -- Design and Development of Ion-Sensitive Field-Effect Transistor and Extended-Gate Field-Effect Transistor Platforms for Chemical and Biological Sensors -- Microactuators: RF MEMS Single-Pole-Multi-Throw switching circuits -- Piezoelectric actuators in helicopter active vibration control -- Design and development of a piezoelectrically actuated micro pump for drug delivery application -- Development and characterization of PZT multi layered stacks for vibration control -- Development of Piezoelectric and Electrostatic RF MEMS devices -- Materials and Processes: Nickel-Titanium Shape Memory Alloy Wires for Thermal Actuators -- Processing and Characterization of Shape Memory Films for Microactuators -- Piezoceramic coatings for MEMS and Structural Health Monitoring -- Cost-effective processing of polymers and application to devices -- Chemical synthesis of nanomaterials and structures, including nanostructured thin films, for different applications -- A Study on Hydrophobicity of Silicon and a few Dielectric Materials.-Materials for Embedded Capacitors, Inductors, Non-reciprocal devices and Solid Oxide Fuel cells in Low Temperature Co-fired Ceramic (LTCC) -- Smart Materials for Energy Harvesting, Energy Storage and Energy Efficient Solid State Electronic Refrigeration -- Modeling and Simulation: Vibratory MEMS and Squeeze Film Effects -- Streaming Potential in Micro flows and Nano flows -- A simulation module for microsystems using hybrid finite elements: an overview -- Structural Health Monitoring: Nonlinear Effects in the Prognostic Analysis of Crack Growth in Structural Joints -- Systems and Applications: Smart e-textile based Nano sensors for Cardiac Monitoring with Smart Phone and Wireless Mobile Platform -- Polymer based Micro/Nano Cantilever Electro-Mechanical Sensor Systems for Bio/Chemical Sensing Applications -- Smart Materials Technology for Aerospace Applications -- Electronic Circuits for Piezoelectric Resonant Sensors -- A Universal Energy Harvesting Scheme for Operating Low-Power Wireless Sensor Nodes using Multiple Energy Resources: Design of Rectennas and Power Management Electronics -- RF MEMS True Time Delay Phase Shifter -- MEMS Sensors for Underwater Applications.
Keywords: Engineering; Mechanical engineering; Nanotechnology; Electronics; Microelectronics; Engineering; Nanotechnology and Microengineering; Electronics and Microelectronics, Instrumentation; Mechanical Engineering; Electronic books